Employee Work Productivity in Managing the E-Letter System at the Secretariat of the Surabaya City DPMPSTP - Naila Zerlinda (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
The digitalization of public administration has become a strategic necessity to enhance bureaucratic efficiency, effectiveness, and accountability, particularly in managing official correspondence that is still largely handled through manual procedures and often constrains employee productivity. The urgency of this study lies in the limited empirical research that examines E-Correspondence systems not merely as technical tools but as determinants of work productivity in public organizations. This study aims to analyze employee work productivity in managing administrative correspondence through the implementation of the E-Correspondence system at the Secretariat of the Surabaya City Investment and One-Stop Integrated Services Agency (DPMPTSP). The study is grounded in e-government and work productivity perspectives within the public sector context. A qualitative case study approach was employed, with data collected through in-depth interviews with purposively selected civil servants directly involved in the use of the system. Data were analyzed using the interactive model of Miles and Huberman. The findings indicate that the E-Correspondence system significantly improves time efficiency, the quality of document outputs, timeliness, and coordination among employees, thereby strengthening individual and team performance. The study highlights the importance of continuous capacity building and system optimization to support productive and accountable public administration